Urolithiasis in dogs: Evaluation of trends in urolith composition and risk factors (2006‐2018). (7th May 2021) - Kopecny, Lucy; Palm, Carrie A.; Segev, Gilad; Westropp, Jodi L.
Abstract: Background: Urolithiasis is a common and often recurrent problem in dogs. Objective: To evaluate trends in urolith composition in dogs and to assess risk factors for urolithiasis, including age, breed, sex, neuter status, urolith location, and bacterial urolith cultures. Sample Population: A total of 10 444 uroliths and the dogs from which they were obtained. Methods: The laboratory database at the UC Davis Gerald V. Ling Urinary Stone Analysis Laboratory was searched for all urolith submissions from dogs between January 2006 and December 2018. Mineral type, age, breed, sex, neuter status, urolith location, and urolith culture were recorded. Trends were evaluated and variables compared to evaluate risk factors. Results: Calcium oxalate (CaOx) and struvite‐containing uroliths comprised the majority of all submissions from dogs, representing 47.0% and 43.6%, respectively. The proportion of CaOx‐containing uroliths significantly decreased from 49.5% in 2006 to 41.8% in 2018 ( P = .006), with no change in the proportion of struvite‐containing urolith submissions. Cystine‐containing uroliths comprised 2.7% of all submissions between 2006 and 2018 and a significant nonlinear increase in this mineral type occurred over time (1.4% of all submissions in 2006 to 8.7% in 2018; P < .001). Of all cystine‐containing uroliths, 70.3% were from intact male dogs. Age, breed, and sex predispositions for uroliths were similar to those previously identified. Conclusions and Clinical Importance: Although calcium oxalate‐ and struvite‐containing uroliths continue to be the most common uroliths submitted from dogs, a decrease in the proportion of CaOx‐containing uroliths and an increase in the proportion of cystine‐containing uroliths occurred during the time period evaluated.